The welfare impact of parallel imports: A structural approach applied to the German market for oral anti-diabetics - Tomaso Duso; Annika Herr; Moritz Suppliet (Deutsches Institut für Wirtschaftsforschung (DIW), 2014)
We investigate the welfare impact of parallel imports using a large panel data set containing monthly information on sales, ex-factory prices, and further product characteristics for all 700 anti-diabetic drugs sold in Germany between 2004 and 2010. We estimate a two-stage nested logit model of demand and, based on an oligopolistic model of multiproduct firms, we then recover the marginal costs and markups. We finally evaluate the effect of the parallel imports' policy by calculating a counter-factual scenario without parallel trade. According to our estimates, parallel imports reduce the prices for patented drugs by 11% and do not have a significant effect on prices for generic drugs. This amounts to an increase in the demand-side surplus by 19 million per year (or 130 million in total) which is relatively small compared to the average annual market size of around 227 million based on ex-factory prices. The variable profits for the manufacturers of original drugs from the German market are reduced by 18 million (or 37%) per year when parallel trade is allowed, yet only one third of this difference is appropriated by the importers.
Keywords: I11; I18; L13; L51; 330; parallel imports; pharmaceuticals; structural models; anti-diabetic drugs